Exploring the Potential of VR Technology in Education in Indonesia - Kinanti, Cinta Sekar (Green Publisher Indonesia, 2024)
This paper explores the impact of Virtual Reality (VR) on teacher training and elementary education, highlighting the improvement in teachers' understanding and skills as well as students' learning motivation. The paper contributes to the understanding of the benefits and potential applications of VR in educational settings, particularly focusing on teaching and elementary school learning. A literature review was conducted to identify previous findings and research gaps related to the implementation of VR. The study was conducted through observations, surveys, and interviews. The collected data were analyzed qualitatively and quantitatively, and the results were used to develop recommendations regarding VR content design, implementation strategies, and supporting policies. Despite challenges such as cost, accessibility, teacher capacity development, and data security, addressing these challenges could enable VR to become a revolutionary learning tool that can improve the quality of education in Indonesia. With the right approach, including relevant content development and further research, VR can become an effective and engaging learning tool in sports education, taking the learning experience to a more interactive and innovative dimension.